A theoretical classification system of helping behavior and helping motives. Issue 5 (1st August 2016) - Chou, Shih Yung; Stauffer, Joseph
Abstract : Purpose: We develop a classification system of helping behavior using the recipient's solicitation and the helper's proactiveness. Additionally, we explore helping motives for each of the forms of helping behavior that we identify. Design/methodology/approach: We examined relevant research and performed a theoretical analysis. Findings: We classified helping behavior into three distinct forms, including unsolicited proactive helping behavior, unsolicited reactive helping behavior, and solicited reactive helping behavior. Additionally, we claim that unsolicited proactive helping behavior is an outcome of personality and dispositions, that unsolicited reactive helping behavior is a process of social and instrumental exchange, and that solicited reactive helping behavior is a product of functional motives. Practical implications: First, from the perspective of organizational justice, we recommend managers to take the form of helping behavior exhibited into consideration when evaluating employees' helping behavior because certain forms of helping behavior require greater degrees of cooperation and sacrifices from the helper than other forms. Second, because employees who engage in high levels of unsolicited proactive helping behavior are likely to experience interrole conflict, we suggest that managers provide counseling and managerial support that help cope with emotional and psychological strain created by excessive role demands. Finally, findings of this study imply that managers need to create a workplace culture where employees can feel comfortable to solicit help when necessary. Originality/value: This is the first study that classifies helping behavior and helping motives using both of the helper and recipient's perspectives.